A mixed methods analysis of existing assessment and evaluation tools (AETs) for mental health applications - Ahmed, Sarah; Trimmer, Chris; Khan, Wishah; Tuck, Andrew; Rodak, Terri; Agic, Branka; Kavic, Kelsey; Wadhawan, Sapna; Abbott, Maureen; Husain, M. Omair; Husain, M. Ishrat; McKenzie, Kwame; et al. (Frontiers in Public Health, 2024)
Mental health Applications (MH Apps) can potentially improve access to high-quality mental health care. However, the recent rapid expansion of MH Apps has created growing concern regarding their safety and effectiveness, leading to the development of AETs (Assessment and Evaluation Tools) to help guide users. This article provides a critical, mixed methods analysis of existing AETs for MH Apps by reviewing the criteria used to evaluate MH Apps and assessing their effectiveness as evaluation tools. To identify relevant AETs, grey and scholarly literature were located through stakeholder consultation, Internet searching via Google and a literature search of bibliographic databases Medline, APA PsycInfo, and LISTA. Materials in English that provided a tool or method to evaluate MH Apps and were published from January 1, 2000, to January 26, 2021 were considered for inclusion. Thirteen relevant AETs targeted for MH Apps met the inclusion criteria. The qualitative analysis of AETs and their evaluation criteria revealed that despite purporting to focus on MH Apps, the included AETs did not contain criteria that made them more specific to MH Apps than general health applications. There appeared to be very little agreed-upon terminology in this field, and the focus of selection criteria in AETs is often IT-related, with a lesser focus on clinical issues, equity, and scientific evidence. The quality of AETs was quantitatively assessed using the AGREE II, a standardized tool for evaluating assessment guidelines. Three out of thirteen AETs were deemed 'recommended' using the AGREE II. There is a need for further improvements to existing AETs. To realize the full potential of MH Apps and reduce stakeholders' concerns, AETs must be developed within the current laws and governmental health policies, be specific to mental health, be feasible to implement and be supported by rigorous research methodology, medical education, and public awareness.